(untitled) (Progressive Agriculture, 2018)
An experiment was carried out at the agronomy field laboratory of Bangladesh Agricultural University, Mymensingh to evaluate the effect of variety and phosphorus on the yield and yield components of groundnut. The experiment comprising of two groundnut varieties viz. BARI Cheenabadam-8 and BINA Cheenabadam-6 and four levels of phosphorus viz. 0, 20, 40 and 60 kg P ha-1. The experiment was laid out in a randomized complete block design with three replications. The highest value of all the parameters e.g. leaf area index (2.02), dry matter (51.88 g plant-1), number of primary branches plant-1 (10.70), number of secondary branches plant-1 (13.85), number of pegs plant-1 (64.35), number of total pods plant-1 (44.50), weight of 100-pods (94.66 g), weight of 100-seeds (44.47 g), shelling percentage (81.84%), seed yield (2.48 t ha-1), pod yield (3.03 t ha-1), stover yield (6.92 t ha-1) and harvest index (30.45%) were recorded from BARI Cheenabadam-8 applied with 60 kg P ha-1. The lowest value of all these parameters was found in BINA Cheenabadam-6 and with no applied phosphorus. It can be concluded that BARI Cheenabadam-8 should preferably be fertilized with 60 kg P ha-1 to obtain the highest yield. Progressive Agriculture 29 (2): 117-126, 2018